Factors affecting the quality and nutritional value of donkey meat: a comprehensive review - Zhang, Wei; Zhang, Min; Sun, Yujiang; Liu, Shuqin (Frontiers in Veterinary Science, 2024)
Donkey meat is characterized by a high content of proteins, essential amino acids, and unsaturated fatty acids and is low in fat, cholesterol, and calories. Thus, it is considered a high-quality source of meat. Based on the data from PubMed and Web of science within past 10 years, this review summarizes the factors affecting the quality of donkey meat and its nutritional value, including breed, genetics, gender, age, muscle type, feeding regimen, storage and processing conditions. Breed, gender, age, and feeding regimen mainly affect the quality of donkey meat by influencing its intramuscular fat content and carcass quality. Meanwhile, the tenderness and flavor of donkey meat depend on the muscle type, storage and processing conditions. Genetics, on the other hand, fundamentally affect donkey meat quality by influencing the polymorphism of genes. These findings provide valuable insights and guidance for producers, consumers, and decision-makers in the donkey meat industry, promoting the development of more effective marketing strategies and the improvement of meat quality, thereby enabling the expansion and progress of the entire industry.